Enfermedad neurológica bovina con diagnóstico no conclusivo en la región norte de Colombia: análisis histológico e inmunohistoquímico - Montoya-Flórez, Luis Mauricio; Ocampo, Pablo Eduardo; Rocha, Noeme Sousa [UNESP]; Pedraza, Francisco Javier (Universidad Nacional de Colombia, 2015)
Bovine neurological disease generates high economic losses in herds and some of its etiological agents are zoonotic, situations that make priority their study. The aim of this study was to identify antigens rabies virus and bovine herpesvirus-5 (BoHV-5) in cattle brain samples archived as cases of neurological disease with no conclusive diagnosis. 10 samples were selected from laboratory of the Colombian Agricultural Institute –ICA– at Monteria. Tissues were analyzed by histopathology and immunohistochemistry techniques. For immunohistochemical analysis, three antibodies were used: two against antigens of rabies virus at a dilution of 1:200, and one against antigens of BoHV-5 at a dilution of 1:100. Histologically lesions i nine cases lesions that varied in type and severity were observed; antigens detection of rabies virus could be demonstrated by immunohistochemistry in 20% (2/10) of cases and could not be demonstrated in any case the presence BoHV-5. We discuss on the histopathological and immunohistochemical finding, it is concluded on the importance of perform association of the two techniques to assist the establishing of the neurological disease etiology, especially in case without diagnostic.

La enfermedad neurológica bovina genera altas pérdidas económicas en las ganaderías y algunos de sus agentes etiológicos son zoonóticos, hechos que hacen prioritario su estudio. El objetivo del trabajo fue identificar antígenos del virus de la rabia y del herpes virus bovino-5 (BoHV-5) en muestras de encéfalos de bovinos archivados como casos de enfermedad neurológica con diagnóstico no conclusivo. Se seleccionaron 10 muestras del laboratorio del Instituto Colombiano Agropecuario –ICA– de Montería. Los tejidos fueron analizados mediante histopatología e inmunohistoquímica; para esta última técnica fueron utilizados tres anticuerpos: dos contra antígenos del virus de la rabia a una dilución de 1:200 y uno contra BoHV-5 a una dilución de 1:100. Histológicamente en nueve casos se observaron lesiones que variaron de tipo y severidad; la identificación de antígenos del virus de la rabia se demostró en 20% (2/10) de los casos y en ningún caso se demostró la presencia BoHV-5. Se discute sobre los resultados histopatológicos e inmunohistoquímicos y se concluye la importancia de asociar los hallazgos de las dos técnicas para establecer la etiología de la enfermedad neurológica, especialmente en casos con diagnóstico inconcluso.
Neurological diseases in cattle with non-conclusive diagnostic in the Colombia northern region: histological and inmunohistochemical analys
Keywords: Immunofluorescence; Inmunohistochemistry; Lyssavirus; Meningoencephalitis; Inmunofluorescencia; Inmunohistoquímica; Lyssavirus; Meningoencefalitis